The Usage of Information System as the Determinant of Successful Implementation of Business Model in Construction Project Based: A Study of Construction Companies in Indonesia - Suroso, Agus; Siti Astuti, Endang; Nayati Utami, Hamidah; Arifin, Zainul (International Journal of Psychosocial Rehabilitation, 2020)
The success business model in construction projects has become an interesting topic to be investigated by the researcher, mainly due to the fact that the failures of the construction companies are rampant. The main problem that has been found from this research is that the opinion of the user in information system (IS) contribution is significant to the projects’ success. Therefore, the objective of this research is to investigate the significant effect of IS on the projects’ success through individuals and organizations. The variables of this research consist of system quality, information quality, intention to use, user satisfaction, and individual impact. All variables were linked and analysed by using Smart PLS3 to investigate the validity, reliability, direct, and indirect effects. The result showed that all variables and indicators are valid, as indicated by the loading factor and AVE value higher than 0.5. Direct effect analysis has a CR value higher than the t-table (2.00), and indirect effect has a t-stat higher than the t-table. It means that all variables and indicators of this research were significant or had a positive effect between variables. This research proved that the usage of the information system contributes significantly towards the success of the implementation of the business model in the construction companies, particularly in West Java, Indonesia.